Les propriétés temporelles des noms abstraits à l'exemple des formations à préfixe « -inter » - Nkollo, Mikołaj (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2005)
The present paper deals with temporal properties of noun phrases whose head is a nominal lexical item with an inter- affix. The whole description is based on the linear concept of time. The key notions used in the following account are precedence in time, momentary thing, interval and coincidence. They originate from mereology. If the inter- prefix is added to a continuous nominal root, the whole noun phrase designates two identical states of affairs or two homogenous activities. The temporal relations holding between them are characterized in terms of overlapping of two intervals. As for nouns that represent non-continuous notions, the inter- affixation results in naming two simultaneous events. The chronology of the latter is described in terms of coincidence of two momentary things. The paper comprises necessary definitions and numerous examples.
Temporal features of French abstract nouns. The case of inter- prefix forms